Rancang Bangun Aplikasi Penjadwalan Proyek Pada PT. Bintang Timur Nangendi Dengan Menggunakan Crithical Path Method - Setiawan, Wahyu Indra; tiowati, Sulis; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
ABSTRACT: PT. Nangendi Eastern Star is a company engaged in construction that handles multiple building projects from government and private sources. During this time, companies are experiencing delays in completing the project scheduling. This is because in determining the scheduling time projects that are still based on the approximate part of the project manager. So companies are experiencing delays in completing projects already scheduled.Based on these problems, they invented scheduling information system projects using methods Critical Path Method. In such systems aim to schedule in accordance with determining the critical path of a project so that the project manager can carry out the project activities in accordance with the project schedule known critical path with Critical Path Method.The information system is made to produce a report that displays the scheduling of project activities on the critical path. Under the system of information created and a series of trials that have been done, the company can find information needed, especially concerning the determination of the Critical Path. So that the company can determine where an activity is preferred phase project work.